ANALISIS KEPUTUSAN KONSUMEN DALAM MEMBELI AYAM RAS PEDAGING (Gallus domesticus) DI KOTA BATURAJA KABUPATEN OGAN KOMERING ULU (JASEP, 2019)
This study aims to analyze the factors that influence consumer decisions in buying broiler in Kota Baturaja. This research is conducted in traditional market in Baturaja City that is Pasar Atas and Pasar Baru. Data Collection The research was conducted by survey method using 30 samples. Sampling method used in this research is Accidental Random Sampling. Data processing method using Binary Logistic Regression Analysis. The results of this study can be concluded that Factors that have a significant effect on the chances of consumers buying broilers (Gallus domesticus) in the city of Baturaja which is the price of broiler (X1), laying chicken (X2), education (X5), the amount (X6), income (X7), appetite (D1) and quality (D2) and factors that have no significant effect on the chances of consumers buying broilers in Baturaja City, namely the price of chicken (X3) and the price of the domestic egg (X4)